1994
DOI: 10.1080/03079459408419021
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte subpopulations in kidney and trachea of chickens infected with infectious bronchitis virus

Abstract: SUMMARYUsing immunohistochemical methods, we studied the nephropathogenicity of the infectious bronchitis virus (IBV)-strain V1648-and the leukocyte phenorypes in the pathological lesions in the kidneys and the trachea formed after inoculation with this virus strain. One-day-old WLA chickens were intravenously inoculated, and after 5, 7 and 11 days their kidneys, trachea and lungs were removed. Monoclonal antibodies were used to detect viral antigen, and lymphoid and non-lymphoid cell populations. In serial se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 31 publications
4
18
0
2
Order By: Relevance
“…If air sac involvement occurs, there is edema, epithelial cell desquamation, and some fibrinous exudates within 24 hrs (Riddell, 1987). Janse et al, (1994) also reported the comparable findings like deciliation, sqamous metaplasia, cellular infiltration, edema of mucous and exudates as noticed by other workers (Butcher et al, 1990;Mahdavi et al, 2007). The virus replicates in ciliated epithelial cells causing deciliation, odema, desquamation, hyperplasia and mononuclear cell infiltration.…”
Section: Resultssupporting
confidence: 70%
“…If air sac involvement occurs, there is edema, epithelial cell desquamation, and some fibrinous exudates within 24 hrs (Riddell, 1987). Janse et al, (1994) also reported the comparable findings like deciliation, sqamous metaplasia, cellular infiltration, edema of mucous and exudates as noticed by other workers (Butcher et al, 1990;Mahdavi et al, 2007). The virus replicates in ciliated epithelial cells causing deciliation, odema, desquamation, hyperplasia and mononuclear cell infiltration.…”
Section: Resultssupporting
confidence: 70%
“…The performance of the IPA in detecting IBV antigen after inoculation of SPF chickens compares very favourably with IFA (Nakamura et al, 1991;Owen et al, 1991;Janse et al, 1994;Chen et al, 1996). Naqi (1990) showed that IBV could be detected by IPA in the CAM of inoculated eggs within 15 h p.i., with a detection limit of 10 6.2 EID 50 .…”
Section: Detection Of Ibv Antigenmentioning
confidence: 88%
“…IBV strains that have been shown to be of different serotypes by VN may be able to induce partial or complete immunity in chickens (Hitchner et al ., 1964;Raggi & Lee, 1965;Winterfield et al ., 1972;Darbyshire, 1980Darbyshire, , 1985Arvidson et al ., 1990). The broader degree of cross-protection in birds is likely to be related to the cellmediated immune responses to shared T-cell epitopes among some heterologous strains (Janse et al ., 1994;Dhinakar Raj & Jones, 1997;Collisson et al ., 2000;Seo et al ., 2000).…”
Section: Discussionmentioning
confidence: 99%